2022
DOI: 10.3390/cells11020199
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy Regulation Following Myocardial Infarction

Abstract: Mitophagy, which mediates the selective elimination of dysfunctional mitochondria, is essential for cardiac homeostasis. Mitophagy is regulated mainly by PTEN-induced putative kinase protein-1 (PINK1)/parkin pathway but also by FUN14 domain-containing 1 (FUNDC1) or Bcl2 interacting protein 3 (BNIP3) and BNIP3-like (BNIP3L/NIX) pathways. Several studies have shown that dysregulated mitophagy is involved in cardiac dysfunction induced by aging, aortic stenosis, myocardial infarction or diabetes. The cardioprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 115 publications
0
18
0
Order By: Relevance
“…Mitochondrial dysfunction is a key feature of IR injury [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and the pan-inhibition of δPKC, with δV1-1, prevents IR-induced increases in mitochondrial oxidant production, and decreases in ATP levels [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, the mechanism by which δPKC causes mitochondrial dysfunction, and the protein substrate that mediates it, have not been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial dysfunction is a key feature of IR injury [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and the pan-inhibition of δPKC, with δV1-1, prevents IR-induced increases in mitochondrial oxidant production, and decreases in ATP levels [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, the mechanism by which δPKC causes mitochondrial dysfunction, and the protein substrate that mediates it, have not been identified.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, increasing evidence suggests that modulation of mitophagy plays a pivotal role during myocardial IRI (11), and it may become a novel target for cardioprotection. The PINK1/Parkin signaling pathway is the most recognized pathway leading to mitophagy in mammalian cells (29). PINK1, a serine/threonine kinase, is imported from the cytoplasm to the inner mitochondrial membrane in healthy mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that under normal conditions, PINK1 enters the inner membrane with the help of protein transporters and is continuously cleaved and decomposed by proteins in the inner membrane of mitochondria, and finally transported to the cytoplasm [28]. However, in dysfunctional mitochondria, the cutting process of PINK1 is stopped and accumulates in the outer membrane of mitochondria [29].…”
Section: Discussionmentioning
confidence: 99%